Analysis of Kidney Function Test Profiles in Relation to the Incidence of Chronic Kidney Failure in Diabetes Mellitus Patients - Pauzi, Iswari; Hadi, Aprilia Khairunnisa; Diarti, Maruni Wiwin (Jurnal Analis Medika Biosains (JAMBS), 2025)
Diabetes Mellitus (DM) is one of the most common chronic diseases worldwide and is a leading cause of chronic kidney failure (CKD). Kidney complications in diabetic patients, known as diabetic nephropathy, can lead to CKD. Early detection and monitoring of kidney function are crucial in managing patients with DM to prevent or delay the progression of CKD. Kidney function tests such as urea levels, creatinine levels, and uric acid levels can be used to assess kidney condition and the risk of CKD development. To analyze the profile of kidney function tests in cases of chronic kidney failure in patients with diabetes mellitus. This study is an Analytical Observational research. The number of samples of diabetes mellitus patients with chronic kidney failure is 52 patients who underwent kidney function profile examinations including urea, creatinine, and uric acid. The data analysis used is descriptive analysis. Based on the obtained data, it was found that during this study, the respondents were predominantly male, with 36 individuals (69.2%), and in terms of age group, the respondents were predominantly in the 61-70 age group, with 15 individuals (28.8%). The average values of urea, creatinine, and uric acid in 52 samples of diabetes mellitus patients with chronic kidney failure were 123.05 mg/dl for urea, 4.85 mg/dl for creatinine, and 8.35 mg/dl for uric acid. The characteristics of the respondents based on gender were predominantly male, and the characteristics based on age were predominantly within the 61-70 year age group. The analysis results showed an increase in the values of kidney function test profiles (urea, creatinine, and uric acid) in diabetic patients with chronic kidney failure. It is evident from the average results of each kidney function test parameter that the average levels exceeded the normal range.